dipm: an R package implementing the Depth Importance in Precision Medicine (DIPM) tree and Forest-based method - Chen, Victoria; Li, Cai; Zhang, Heping (Bioinformatics advances, 2022)
Summary The Depth Importance in Precision Medicine (DIPM) method is a classification tree designed for the identification of subgroups relevant to the precision medicine setting. In this setting, a relevant subgroup is a subgroup in which subjects perform either especially well or poorly with a particular treatment assignment. Herein, we introduce, dipm, a novel R package that implements the DIPM method using R code that calls a program in C. Availability and implementation dipm is available under a GPL-3 licence on CRAN https://cran.r-project.org/web/packages/dipm/index.html and at https://ysph.yale.edu/c2s2/software/dipm. It is continuously being developed at https://github.com/chenvict/dipm. Supplementary information Supplementary data are available at Bioinformatics Advances online.